Some Elements About the Classical Employment Theory and the Keynesian Perspective - Primera Argoti; George Samuleson (Global Writing Academica Researching & Publishing, 2022)
The fundamental aim of this paper is to lay out essential elements concerning classical economic theory about employment, and compare them with the Keynesian approach. In other words, this document shows a comparative-contrasting study of the classical and more modern theoretical claims, concerning employment. Since employment is a crucial variable related to economic growth and development, this paper is focused on a revision of conceptual issues concerning such a critical indicator. The approach presented here is important not only for professional economists but also for other social scientists. One of the major conclusions of this study is referred to the evidence that the Keynesian “General Theory” is not precisely the most completed and updated theoretical approach to solve problems of employment, but it has a particular richness in its contents that is important to rescue; in fact that theory was extremely useful to undertake unemployment and economic growth problems during the Great Recession in the United States.